Level of Knowledge on Radiation Protection in Roentgen Photo-taking among Clinical Dental Students - Kemala HAYATI; Herwanda HERWANDA; Yusmar YUSMAR (Journal of Syiah Kuala Dentistry Society, 2022)
Radiography in dentistry is a device that is often used. The images produced from radiographs aresignificant for dentists, especially to see any abnormalities that are not visible or unclear on clinical examination sothat they can assist in making a diagnosis, determining treatment plans, and assessing treatment success. Besideshaving benefits, radiography can also cause damage to normal human cells or tissues. The danger caused by thisradiation can be overcome by radiation protection. This study aimed to determine the knowledge of clinicalclerkship students regarding radiation protection when taking dental x-rays at the Dental and Oral Hospital ofUniversitas Syiah Kuala (RSGM). This type of research is descriptive, with a total of 305 subjects. The data wasCollected through the distribution of questionnaires. The results showed that there were 44 (14.4%) students whohad a high level of knowledge, 159 (52.1%) moderate, and 102 (33.4%) low. It was concluded that most youngdentists at RSGM had an intermediate level of knowledge about radiation protection when taking x-rays.KEYWORDS: Radiography, radiation protection, level of knowledge, Clinical Clerkship Students